High number of kinome‐mutations in non‐small cell lung cancer is associated with reduced immune response and poor relapse‐free survival. Issue 1 (21st April 2017) - Helland, Å.; Brustugun, O. T.; Nakken, S.; Halvorsen, A. R.; Dønnem, T.; Bremnes, R.; Busund, L. T.; Sun, J.; Lorenz, S.; Solberg, S. K.; Jørgensen, L. H.; Vodak, D.; et al.
Abstract : Lung cancer is the leading cause of cancer related death, and the past years' improved insight into underlying molecular events has significantly improved outcome for specific subsets of patients. In particular, several new therapies that target protein kinases have been implemented, and many more are becoming available. We have investigated lung cancer specimens for somatic mutations in a targeted panel of 612 human genes, the majority being protein kinases. The somatic mutation profiles were correlated to profiles of immune cell infiltration as well as relapse‐free survival. Targeted deep sequencing was performed on 117 tumour/normal pairs using the SureSelect Human Kinome kit (Agilent Technologies), with capture probes targeting 3.2 Mb of the human genome, including exons and untranslated regions of all known kinases, kinase receptors and selected cancer‐related genes (612 genes in total). CD8 staining was determined using Ventana Benchmark. Survival analyses were performed using SPSS. The number of mutations per sample ranged from 0 to 50 (within the 612 genes tested), with a median of nine. The prognosis was worse for patients with more than the median number of mutations. A significant correlation was found between mutations in one of selected DNA‐repair genes and the total number of mutations in that tumour ( p  < 0.001). There was a significant inverse correlation between the number of infiltrating stromal CD8+ lymphocytes and the presence of EGFR mutations. Abstract : What's new? Lung carcinomas are among the tumours with highest mutation frequency. Here, the authors performed mutational analyses of 612 genes–including all known kinases and kinase receptors–in 117 non‐small cell lung cancer (NSCLC) tumours. They also investigated the relationship of mutation rate to number of infiltrating lymphocytes and to the clinical course of the disease. The number of mutations per sample varied, and the relapse‐free survival was worse for patients with more than the median number of mutations. Also, there was a significant inverse correlation between the number of infiltrating stromal CD8+ lymphocytes and the presence of EGFR mutations.